INTERTEXTUALITY OF THE COVID-19 MEMES ON INSTAGRAM - Lailan Syafrina Dewi; Evi . Aisyah; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2022)
This study deals with the Intertextuality of the Covid-19 memes on instagram. This study focuses on analysis of types of intertextuality, the discursive practice and the social practice realized in the covid-19 memes. This study conducted by using qualitative method by collecting some memes related to the covid-19 as the data. From this study, we can get the result that the memes which categorize as the quotation are three. The percentage is 60%. The two memes are categorized as convention and configuration and paralogues each one. So, the percentages of convention and configuration are 20% and paralogue, 20%. The total is 100% from the five memes analyzed. The discursive practice and the social practice realized in the memes.